Customary and Legal Principles of Communication in Relation to Unethical Speech Acts - Kowalczyk, Joanna (Respectus Philologicus, 2023)
The present paper discusses the problem of unethical speech acts, verbal aggression and valuing of texts in the context of legal regulations concerning the axiology of communication in a democratic state. The aim of the study was to describe the relationship between linguistic activity and the rules of ethics of expression in the context of Polish cultural-civilisational conditions and legal directives on ethics of expression and to relate forms of linguistic aggression to how they are qualified as prohibited acts that violate the norms of acceptable patterns of communication. The research corpus comes from legal acts and public statements. The legislative corpus was based on two normative texts fundamental for regulating the ethics of social life, i.e. the Constitution of the Republic of Poland (K97) and the Polish Penal Code(KK97). Discursive analysis and legal functional-systemic interpretation constituted the methodological foundation of the study. The analysis showed the expected functionality of a word in the context of a community organised within state structures. On the one hand, a word can be a way of describing reality or emotions, and on the other, an object of legal protection or an instrument of crime.
Keywords: ethics in communication; axiology of expression; linguistic aggression